2003
DOI: 10.1007/bf03018709
|View full text |Cite
|
Sign up to set email alerts
|

Patient controllediv analgesia is an acceptable pain management strategy in morbidly obese patients undergoing gastric bypass surgery. A retrospective comparison with epidural analgesia

Abstract: P Pu ur rp po os se e: : To examine the hypothesis that pain treatment with patient controlled analgesia (PCA) using iv morphine is a suitable and safe alternative to epidural analgesia in morbidly obese patients undergoing gastric bypass surgery. We retrospectively compared the postoperative periods in all patients undergoing this procedure in our institution between November 1999 and November 2001.M Me et th ho od ds s: : According to their perioperative pain treatment, patients were assigned to a PCA group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…En cas de recours à la morphine, l'auto-administration par voie IV est pré-conisée car chez l'obèse, l'injection intramusculaire est associée à des résorptions médicamenteuses imprévisibles. Récemment, l'analgésie autocontrolée (ACP) avec de la morphine IV s'est révélée comme une stratégie d'analgésie acceptable lorsqu'on la compare à l'analgésie péridurale chez des obèses morbides opérés d'un bypass gastrique [49]. L'analgésie péridurale est une alternative à l'ACP mais nécessite une certaine expérience.…”
Section: Réveil Et Période Postopératoireunclassified
“…En cas de recours à la morphine, l'auto-administration par voie IV est pré-conisée car chez l'obèse, l'injection intramusculaire est associée à des résorptions médicamenteuses imprévisibles. Récemment, l'analgésie autocontrolée (ACP) avec de la morphine IV s'est révélée comme une stratégie d'analgésie acceptable lorsqu'on la compare à l'analgésie péridurale chez des obèses morbides opérés d'un bypass gastrique [49]. L'analgésie péridurale est une alternative à l'ACP mais nécessite une certaine expérience.…”
Section: Réveil Et Période Postopératoireunclassified
“…Furthermore, whilst function may appear to be preserved or only moderately affected by the administration of opioids, the stress, inflammatory and metabolic response to the injury produced by surgery, trauma or infection may unmask the underlying mechanisms that are affected by the presence of opioids in this patient population. Though this has not been adequately explored, some differences in the route of opioid administration have been observed in association with infection incidence, with a greater risk of wound infection in patients receiving epidural opioid analgesia than in those receiving intravenous opioid delivery [118]. A careful analysis of the impact of opiate analgesia on the incidence of infectious complications following traumatic injury, surgery or in critically ill patients warrants further study.…”
Section: Introductionmentioning
confidence: 99%
“…When narcotics are needed, IV patient-controlled anesthesia (PCA) is recommended because absorption after intramuscular injection is unpredictable in the obese patient. A recent study showed that IV morphine by PCA was superior to epidural analgesia in obese patients after gastric bypass [49]. Epidural analgesia is an alternative to PCA but the technique requires more experience.…”
Section: Recovery From Anesthesia and Post-operative Periodmentioning
confidence: 96%